The impact of feed supplementations on Asian buffaloes: a review - Mohd Azmi, Amirul Faiz; Ahmad, Hafandi; Mohd Nor, Norhariani; Goh, Yong Meng; Saad, Mohd Zamri; Abu Bakar, Md Zuki; Salleh, Annas; Abdullah, Punimin; Jayanegara, Anuraga; Abu Hassim, Hasliza (MDPI AG, 2021)
With the increase in the global buffalo herd, the use of supplementation in the ruminant feeding has become an important area for many researchers who are looking for an isocaloric and isonitrogenous diet to improve production parameters. In order to improve the performance of the Asian water buffalo, the optimal balance of all nutrients, including energy and protein, are important as macronutrients. Dietary supplementation is one of the alternatives to enhance the essential nutrient content in the buffalo diet and to improve the rumen metabolism of the animal. Researchers have found that supplementation of concentrate and rumen bypass fat could change growth performance and carcass traits without causing any adverse effects on the buffalo growth. Some studies showed that dry matter intake, body condition score and some blood parameters and hormones related to growth responded positively to concentrate and rumen bypass fat supplementation. In addition, changes of feeding management by adding the supplement to the ruminant basal diet helped to increase the profit of the local farmers due to the increased performance and productivity of the animals. Nevertheless, the effects of dietary supplementation on the performance of ruminants are inconsistent. Thus, its long-term effects on the health and productivity of buffaloes still need to be further investigated.